Distribution and descriptive characteristics of the two giant pill millipedes of the genus Sphaerobelum Verhoeff, 1924 (Diplopoda, Sphaerotheriida, Zephroniidae) in Vietnam - Anh, Nguyen Duc; Sierwald, Petra (Academia Journal of Biology, 2019)
Two giant pill millipedes, Sphaerobelum clavigerum Verhoeff, 1924 and Sphaerobelum hirsutum Verhoeff, 1924, were described from unindicated localities in northern Vietnam. The paper presents the recorded localities, descriptions and colour illustrations of those giant pill millipedes. S. clavigerum Verhoeff, 1924 is recorded from Cuc Phuong National Park (Ninh Binh Province), and distinguished from its congeners by body being shiny, glabrous, anterior telopods 3-segmented, process of 2nd podonomere of posterior telopods slender, not apically strongly swollen. In contrast, S. hirsutum Verhoeff, 1924 is found in Tam Dao National Park and Me Linh Biodiversity Station (both in Vinh Phuc Province), and recognized by body being densely hairy, process of 2nd podonomere of posterior telopods apically strongly swollen, spherical, wider than basis of 3rd podomere. In addition, a key to genera of giant pill millipedes is also provided for the Vietnam fauna.